1983
DOI: 10.1021/es00110a009
|View full text |Cite
|
Sign up to set email alerts
|

Partition equilibriums of nonionic organic compounds between soil organic matter and water

Abstract: Equilibrium isotherms for the simultaneous uptake of binary nonionic organic compounds from water on soil indicated no competitive effect between the two solutes.This observation supports the hypothesis that partition to the soil organic phase is the primary process for sorption of nonionic organic compounds from water on soil. The partition process between soil organic matter and water was analyzed by using the conventional solution concept for solutes in water and the Flory-Huggins treatment for solutes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
643
3
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 985 publications
(694 citation statements)
references
References 26 publications
37
643
3
5
Order By: Relevance
“…It is interesting to note that, if the same pH value is considered, peat has greater sorption capacity than soil, though only 0.10 g peat was used in comparison with 0.40 g soil. As described by Chiou et al (1983), the sorption of organic contaminants especially hydrophobic organic chemicals (HOCs) from water to most soils is due primarily to the partitioning into soil organic matter. Comparing the organic-carbon-normalized partition coefficients (K oc ) (Table 2), it is also found that the K oc values on peat are higher than that of soil, which means peat has greater sorption capacity for 2,4,6-TCP.…”
Section: Effect Of Ph On Sorptionmentioning
confidence: 99%
“…It is interesting to note that, if the same pH value is considered, peat has greater sorption capacity than soil, though only 0.10 g peat was used in comparison with 0.40 g soil. As described by Chiou et al (1983), the sorption of organic contaminants especially hydrophobic organic chemicals (HOCs) from water to most soils is due primarily to the partitioning into soil organic matter. Comparing the organic-carbon-normalized partition coefficients (K oc ) (Table 2), it is also found that the K oc values on peat are higher than that of soil, which means peat has greater sorption capacity for 2,4,6-TCP.…”
Section: Effect Of Ph On Sorptionmentioning
confidence: 99%
“…Lately, more attention has been given to applications of QSARs to predict sorption parameters at the soil or sediment interface (Meylan et al, 1992) because such parameterisation can help in a variety of situations including prediction of local and regional impact of aquatic environment, understanding relative importance of fate (Baker et al, 1997) and transport processes in aquatic systems such as oceans, rivers, aquifers, and lakes, remediation of soils, sediments, and aquifers, bioaccumulation, biomagnification, toxicity to life forms, and bioavailability. Some of the most commonly used QSARs for prediction of sorption capacities at the soil-water interface include the octanol-water partitioning coefficient model (Means et al, 1980;Karickhoff, 1981;Piwomi and Banerjee, 1989;Chiou, 1983;Schwarzenbach et al, 1993), the Linear Solvation Energy model (Nirmalakhandan and Speece, 1993;Luehrs et al, 1996), Molecular Connectivity Indices model (Blum et al, 1994;Nirmalakhandan and Speece, 1988;Xu and Nirmalakhandan, 1998); the Solvophobic Theory (Belfort et al, 1984); and the combination of polarisability parameter, molecular connectivity index, and hydrogen bonding index model (Nirmalakhandan et al, 1997). All these QSARs have essentially tried to focus on several complex physico-chemical surface interactions including adsorption, absorption, ion exchange, pore diffusion, redox reaction, precipitation, dissolution, acid/base hydrolysis, formation of co-ordinated complexes giving rise to the polynuclear species (Weber et al, 1991;Banerji et al, 1993;Gao et al, 1998).…”
mentioning
confidence: 99%
“…The reasons that log k 0 w is 23% larger than log k 0 0 could be explained as follows. The organic matter in soil is a three-dimensional network of polymer chains with a relatively open, flexible structure perforated with ''voids'' (Chiou et al, 1983;Nkedi-kizza et al, 1989). when water is used as an eluent, the polymer layer is in a relatively condensed state.…”
Section: Effect Of Methanol On Column Performancementioning
confidence: 99%
“…It is known that the sorption coefficients (K d ) increase with increasing the organic carbon content in soil (Chiou et al, 1983). Refer to Eq.…”
Section: Retention Equationmentioning
confidence: 99%